2007
DOI: 10.1016/j.neuroscience.2007.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal dopamine D1 antagonism dampens neural plasticity in response to motor cortex lesion

Abstract: Motor cortex lesions in rats partially denervate the striatum, producing behavioral deficits and inducing reactive neuroplasticity. Plastic responses include changes in growth-associated protein marker expression and anatomical restructuring. Corticostriatal plasticity is dependent on dopamine at the striatal target, where D1 receptor signaling reinforces behaviorally relevant neural activity. To determine whether striatal dopamine D1 receptor signaling is important for the growth-associated protein responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…Consistent with these findings, a study in rats showed positive synaptophysin immunostaining in the cerebral cortex of the undamaged hemisphere 1) . Also adding support to these findings, the level of expression of GAP-43 and SCG10, which are proteins involved in the axonal sprouting response, were higher in the cerebral cortex of the undamaged hemisphere than in the damaged hemisphere 6) . Taken together, these findings suggest that the undamaged hemisphere is involved in functional improvement after brain injury.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with these findings, a study in rats showed positive synaptophysin immunostaining in the cerebral cortex of the undamaged hemisphere 1) . Also adding support to these findings, the level of expression of GAP-43 and SCG10, which are proteins involved in the axonal sprouting response, were higher in the cerebral cortex of the undamaged hemisphere than in the damaged hemisphere 6) . Taken together, these findings suggest that the undamaged hemisphere is involved in functional improvement after brain injury.…”
Section: Discussionsupporting
confidence: 53%
“…Clinical studies in which stroke patients were examined by positron emission tomography (PET) or magnetic resonance imaging (MRI) show that the undamaged hemisphere is activated when hemiplegic limbs are moved 4,5) . In animal studies, proteins important for neuronal plasticity were found to increase in the cerebral cortex of the undamaged hemisphere following brain injuries 1,6) . The primary motor area i s a c r u c i a l r e g i o n r e g u l a t i n g v o l u n t a r y movements 7) .…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned evidence suggests that the dopaminergic system in the striatum is altered after TBI and that functional recovery is modulated by a D 1 R-dependent mechanism ( Davis et al, 2007 ). Nevertheless, further studies on the striatum are needed to determine D 2 R function after TBI.…”
Section: Striatal Dopaminergic Disruption After Tbimentioning
confidence: 99%
“…The number of prediction errors is therefore related to discrepancies between expectations and outcomes. Positive and negative prediction errors both induce synaptic plasticity in cortical and subcortical structures including the primary motor cortex (M1), leading to reinforcement of existing behaviors or selection of new behaviors (Calabresi, Picconi, Tozzi, & Di Filippo, ; Centonze et al., ; Davis, Coyne, & McNeill, ; Lang et al., ; Molina‐Luna et al., ; Wickens, Reynolds, & Hyland, ). Therefore, the impact of positive and negative outcomes has been explored at the corticospinal and behavioral levels.…”
Section: Introductionmentioning
confidence: 99%